2019
DOI: 10.1161/jaha.119.012184
|View full text |Cite
|
Sign up to set email alerts
|

Fondaparinux Sodium Compared With Low‐Molecular‐Weight Heparins for Perioperative Surgical Thromboprophylaxis: A Systematic Review and Meta‐analysis

Abstract: Background Fondaparinux sodium has been compared with low‐molecular‐weight heparins ( LMWH ) in randomized controlled trials for perioperative surgical thromboprophylaxis. However, the results from these studies are inconsistent in terms of efficacy and safety to reach a clinical decision. The objective of this study was to systematically review the randomized controlled trials comparing the efficacy and safety of fondaparinux and LMWH for peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…A systematic review and meta-analysis in 2019 suggests that fondaparinux is significantly superior to LMWH in reducing VTE for perioperative arthroplasty surgery [ 7 ]. However, the authors of that review advise that clinicians be aware of the higher risk of major bleeding, especially surgical site bleeding, with fondaparinux [ 7 ].…”
Section: Statements Of Group 3: Pharmacological Venous Thromboembolism Prophylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review and meta-analysis in 2019 suggests that fondaparinux is significantly superior to LMWH in reducing VTE for perioperative arthroplasty surgery [ 7 ]. However, the authors of that review advise that clinicians be aware of the higher risk of major bleeding, especially surgical site bleeding, with fondaparinux [ 7 ].…”
Section: Statements Of Group 3: Pharmacological Venous Thromboembolism Prophylaxismentioning
confidence: 99%
“…A systematic review and meta-analysis in 2019 suggests that fondaparinux is significantly superior to LMWH in reducing VTE for perioperative arthroplasty surgery [ 7 ]. However, the authors of that review advise that clinicians be aware of the higher risk of major bleeding, especially surgical site bleeding, with fondaparinux [ 7 ]. A meta-analysis of four randomized controlled trials (RCTs) showed that fondaparinux significantly reduced VTE incidence compared with enoxaparin in major orthopedic surgery [ 8 ].…”
Section: Statements Of Group 3: Pharmacological Venous Thromboembolism Prophylaxismentioning
confidence: 99%
“…Pooled analysis of 12 randomised control trials involving 14,906 patients found that the odds of VTE in the fondaparinux group were 0.49 times the odds in LMWH group (Odd ratio, OR = 0.49; 95% confidence interval, CI, 0.38-0.64; p < 0.001). Kumar et al found that fondaparinux was associated with increased risk of major bleeding, especially involving surgical site (OR = 1.48; 95% CI, 1.15-1.90; p = 0.002) (Kumar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is insufficient data to support routine use of fondaparinux in pregnancy except for cases such as heparin-induced thrombocytopenia or severe allergy to heparin (Dempfle, 2004;Knol et al, 2010). Fondaparinux has been extensively studied as surgical thromboprophylaxis, however research on its role as in postpartum VTE prevention has been limited to retrospective studies (Kawaguchi et al, 2017;Kumar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The sulfate-containing synthetic pentasaccharide 1 with the sequence d -GlcNS6S-α-(1,4)- d -GlcA-β-(1,4)- d -GlcNS3,6S-α-(1,4)- l -IdoA2S-α-(1,4)- d -GlcNS6S-OMe was identified as the AT-binding sequence and later was introduced into the market in 2002 with the trade name “Fondaparinux (Arixtra)” (Figure ). Fondaparinux was shown to have a faster anticoagulation response, higher and more predictable anti-Xa activity, a longer half-life, a longer duration of action, a lower risk of heparin-induced thrombocytopenia (HIT), and better biosafety compared to those of LMWH, making it a more acceptable anticoagulant . In addition, the contamination in naturally occurring heparins that caused several deaths in 2008 led to the increasing clinical use of Fondaparinux as an alternative and perhaps better anticoagulant.…”
mentioning
confidence: 99%